Indothrix Krombein, 1957 (Hymenoptera, Chrysididae) newly recorded genus from China, with description of one new species - Li, Shuang-Shuang; Xu, Zai-Fu (Zootaxa, 2016)
The genus Indothrix Krombein, 1957 is newly recorded from China. Indothrix brevicornis Li & Xu, sp. nov. (China: Zhejiang) is described and illustrated. Key to the three world species of the genus is given.